2016
DOI: 10.7717/peerj.2662
|View full text |Cite
|
Sign up to set email alerts
|

Simplified large African carnivore density estimators from track indices

Abstract: BackgroundThe range, population size and trend of large carnivores are important parameters to assess their status globally and to plan conservation strategies. One can use linear models to assess population size and trends of large carnivores from track-based surveys on suitable substrates. The conventional approach of a linear model with intercept may not intercept at zero, but may fit the data better than linear model through the origin. We assess whether a linear regression through the origin is more appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Furthermore, habituation can invalidate such calibrations, if animals reduce their response through time. To avoid this problem, track or spoor surveys are widely used to estimate population densities of many of the African large carnivores: lions, hyaenas, leopards, cheetahs, and African wild dogs (Bauer et al, , , ; Hanssen, Funston, Alfred, & Alfred, ; Funston et al, , ; Groom & Watermeyer, ; Houser, Somers, & Boast, ; Midlane, Justin O'Riain, Balme, & Hunter, ; Stander, ; Winterbach, Ferreira, Funston, & Somers, ). Stander () found a positive correlation between track frequency and independent estimates of population density for African wild dogs, leopards, and lions in northern Namibia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, habituation can invalidate such calibrations, if animals reduce their response through time. To avoid this problem, track or spoor surveys are widely used to estimate population densities of many of the African large carnivores: lions, hyaenas, leopards, cheetahs, and African wild dogs (Bauer et al, , , ; Hanssen, Funston, Alfred, & Alfred, ; Funston et al, , ; Groom & Watermeyer, ; Houser, Somers, & Boast, ; Midlane, Justin O'Riain, Balme, & Hunter, ; Stander, ; Winterbach, Ferreira, Funston, & Somers, ). Stander () found a positive correlation between track frequency and independent estimates of population density for African wild dogs, leopards, and lions in northern Namibia.…”
Section: Introductionmentioning
confidence: 99%
“…Funston et al () refined this method to account for substrate variation and concluded that “a combined model for all carnivore species on sandy soils served as a robust approach to predict large carnivore densities.” The regression model of Funston et al () included a nonzero intercept, which allows a track density of zero to predict a population density above zero. Winterbach et al () refined the model by dropping the nonzero intercept from the regression, but did not alter the way the uncertainty in the estimates were calculated; this methodology is hereafter what we refer to as the track count method.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the assumption of constant day range is implicitly assumed whenever spatial–temporal comparisons of repeat spoor surveys are made, including index‐density calibration approaches (e.g. Winterbach et al, ), unless re‐calibrated to local conditions every survey. The extent by which average day range fluctuates from year to year requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Spoor tracking is an index widely used globally (Norris, Peres, Michalski, & Hinchsliffe, ; Southgate & Moseby, ; Winterbach, Ferreira, Funston, & Somers, ). However, to date, this method has mostly been used for monitoring carnivore mammals (Bauer, Schiess‐Meier, Mills, & Gusset, ; Fabiano, ; Gusset & Burgener, ) owing to the difficulty detecting and counting them by other means.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation